Karsinoma sel basal tipe nodular yang diterapi dengan bedah eksisi elips dan anastesi tumesen - I Gusti Nyoman Darmaputra; Made Wardhana; I Gde Nengah Adhilaksman; I Gusti Ayu Agung Elis Indira; Nyoman Suryawati (Intisari Sains Medis, 2019)
Background: Basal cell carcinoma (BCC) has a very slow-growing and rarely metastatic nature but tends to be locally invasive and relapse after therapy. Elliptical excision is one of the surgical procedures in the field of dermatology which is most often used with the application of tumescent techniques.Case Description: A woman, 64 years old, no. CM. 18.03.11.71, Balinese tribe, on July 30, 2018, came to the Dermatology and Venerology Polyclinic at Sanglah General Hospital with a frequent symptom of arising from wounds on the forehead. The lession began one year ago. Initially, it was a small reddish lump which was then felt more and more dilated as well as became blackish and accompanied by itching. Dermatology examination revealed hyperpigmentation, solitary, oval, 3x2cm, multiple erosion, firm boundary, round shape, 0.3-0.4 cm in diameter, covered in black crusting on top.Conclusion: The diagnosis of BCC determined on anamnesis, physical examination, dermoscopy, and histopathology regard with standard ellipse excision surgery.